Boric acid modified starch polyvinyl alcohol matrix for slow release fertilizer - Lum, Yip Hing; Shaaban, Azizah; Mohamad, Noraiham; Dimin @ Mohd Amin, Mohd Fairuz; Mohamad Yatim, Norazlina (De Gruyter, 2016)
The slow release urea fertilizer was prepared by the boric acid crosslinked starch/polyvinyl alcohol (SPB) matrix as biodegradable carrier material. Using a two level factorial design of experiment, a comprehensive understanding of the concentration of boric acid, reaction time and heating temperature in the preparation of SPB matrix was obtained. The swelling ratio, release profile of urea in water, and crushing strength were selected as the response. The interaction between the variables and response was analyzed using the ANOVA model. The system was confirmed using the constant determination, R2 with values above 0.99. The high concentration of boric acid with a prolonged reaction time at high temperature gave relative good results of swelling ratio, dissolution rate of urea and crushing strength. In the 28-day soil incubation experiment, the retention of exchangeable ammonium ion (NH4+) was significant higher in SPB urea as compared to pure urea. There was a potential for SPB matrix to improve nitrogen efficiency by increasing the accumulation of exchangeable NH4+ and decreasing the dissolution rate of urea in the flooded condition.